2015
DOI: 10.1016/j.cell.2015.10.065
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Protein Interaction Landscape of the Human Centrosome-Cilium Interface

Abstract: Summary Centrioles coordinate the primary microtubule organizing center of the cell and template the formation of cilia, thereby operating at a nexus of critical cellular functions. Here we use proximity-dependent biotinylation (BioID) to map the centrosome-cilium interface; with 58 bait proteins we generate a protein topology network comprising >7000 interactions. Analysis of interaction profiles coupled with high resolution phenotypic profiling implicates a number of new protein modules in centriole duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
528
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(588 citation statements)
references
References 46 publications
39
528
2
1
Order By: Relevance
“…3). Consistent with previous studies (20,59), the biological replicates in Flp-In T-REx HeLa lines were highly similar, with R 2 =0.99 across all prey proteins identified and R 2 =0.96 when only the high-confidence preys were considered (Fig. 3A).…”
Section: Lentiviral Bioid Yields Highly Reproducible Resultssupporting
confidence: 89%
“…3). Consistent with previous studies (20,59), the biological replicates in Flp-In T-REx HeLa lines were highly similar, with R 2 =0.99 across all prey proteins identified and R 2 =0.96 when only the high-confidence preys were considered (Fig. 3A).…”
Section: Lentiviral Bioid Yields Highly Reproducible Resultssupporting
confidence: 89%
“…Among these hits is the retinal degeneration gene CCDC66 (Dekomien et al, 2010;Gerding et al, 2011). CCDC66 has been reported to localize to centriolar satellites (Gupta et al, 2015) and its mRNA has been found to interact with microtubules in a screen for microtubule-binding transcripts in Xenopus laevis egg extracts (Sharp et al, 2011). CCDC66 was also previously identified a proximity partner of the canonical satellite protein PCM1 (Gupta et al, 2015), but not for CCDC14 and KIAA0753, which regulate centriole duplication (Firat-Karalar and Stearns, 2015).…”
Section: Proximity Mapping Identifies New Centriolar Satellite Proteinsmentioning
confidence: 99%
“…CCDC66 has been reported to localize to centriolar satellites (Gupta et al, 2015) and its mRNA has been found to interact with microtubules in a screen for microtubule-binding transcripts in Xenopus laevis egg extracts (Sharp et al, 2011). CCDC66 was also previously identified a proximity partner of the canonical satellite protein PCM1 (Gupta et al, 2015), but not for CCDC14 and KIAA0753, which regulate centriole duplication (Firat-Karalar and Stearns, 2015). Based on its proximity to regulators of ciliogenesis, disease link and cellular localization, we chose CCDC66 for further study.…”
Section: Proximity Mapping Identifies New Centriolar Satellite Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene-environment analysis reported that MOSPD2 may be related to the obesity traits among postmenopausal African-American and Hispanic women [4]. This gene is also involved in the dynamic protein interaction of the human centrosome-cilium interface [5].…”
Section: Introductionmentioning
confidence: 99%